Effectiveness of physiotherapy with telerehabilitation in surgical patients: a systematic review and meta-analysis. Issue 3 (September 2018) - van Egmond, M.A.; van der Schaaf, M.; Vredeveld, T.; Vollenbroek-Hutten, M.M.R.; van Berge Henegouwen, M.I.; Klinkenbijl, J.H.G.; Engelbert, R.H.H.
Abstract: Background: Over the last few years, telerehabilitation services have developed rapidly, and patients value benefits such as reduced travelling barriers, flexible exercise hours, and the possibility to better integrate skills into daily life. However, the effects of physiotherapy with telerehabilitation on postoperative functional outcomes compared with usual care in surgical populations are still inconclusive. Objectives: To study the effectiveness of physiotherapy with telerehabilitation on postoperative functional outcomes and quality of life in surgical patients. Data sources: Relevant studies were obtained from MEDLINE, EMBASE, CINAHL, the Cochrane Library, PEDro, Google Scholar and the World Health Organization International Clinical Trials Registry Platform. Study selection: Randomised controlled trials, controlled clinical trials, quasi-randomised studies and quasi-experimental studies with comparative controls were included with no restrictions in terms of language or date of publication. Data extraction and synthesis: Methodological quality was assessed using the Cochrane risk of bias tool. Twenty-three records were included for qualitative synthesis. Seven studies were eligible for quantitative synthesis on quality of life, and the overall pooled standardised mean difference was 1.01 (95% confidence interval 0.18 to 1.84), indicating an increase in favour of telerehabilitation in surgical patients. Limitations: The variety in contents of intervention and outcome measures restricted the performance of a meta-analysis on all clinical outcome measures. Conclusions: Physiotherapy with telerehabilitation has the potential to increase quality of life, is feasible, and is at least equally effective as usual care in surgical populations. This may be sufficient reason to choose physiotherapy with telerehabilitation for surgical populations, although the overall effectiveness on physical outcomes remains unclear. PROSPERO registration number: CRD42015017744.